Stallу Estimation of the Initial Trajectory of Motion in the Problem of Identification of Dynamic Systems Based on the Quasilinearization Method - Zakirovich Igamberdiev, Husan; Muhtarhodjaevna Abdurahmanova, Yulduz (International Journal of Psychosocial Rehabilitation, 2020)
The problems of formation and construction of stable algorithms for estimating the initial trajectory of motion in the problem of identification of dynamic systems based on the quasilinearization method are considered. In constructing stable computational estimation procedures, a projection algorithm is used to solve systems of linear algebraic equations based on the conceptions of the matrix pseudo-inversion. The given stable algorithms are very effective in solving practical problems of identifying control objects in real time.